Rola współczesnej szkoły w zakresie profilaktyki uzależnień od substancji szkodliwych - Wawrzyniak, Sonia (Studia Edukacyjne, 2020)
The essence of the article is to draw attention to the importance of preventive measures in the field of addiction to harmful substances undertaken in schools towards children and youth. The results of a pilot study conducted for one of the schools as part of the diagnosis of phenomena related to the occurrence and use of psychoactive substances by adolescents will be presented. In view of the growing number of problem behaviors among children and adolescents and the threats to their development and health, the issues raised are extremely important. The range of occurrence and the reduced initiation limit of reaching for harmful substances are a difficult problem for modern pedagogy, psychology, sociology and therapy. Strengthening preventive actions is a challenge for the modern school, for which the priority should be to care for the integral and multilateral development of students. The school period is for a child and a young person an important time of changes in the spheres of development and shaping of identity and personality. It is important that young people receive support to help them solve problems and avoid risky behavior.